PENERAPAN SPA KAKI DIABETIK TERHADAP SIRKULASI DARAH PERIFER PADA PASIEN DIABETES MELLITUS TIPE 2DI WILAYAH BINAAN PUSKESMAS ROWOSARI SEMARANG: THE IMPLEMENTATION OF DIABETIC FEET SPA FOR PERIFER BLOOD CIRCULATION IN TYPE 2 DIABETES MELLITUS PATIENTS IN THE BINAAN REGION OF PUSKESMAS ROWOSARI SEMARANG - Diyan Pratama Sari; Diana Dayaningsih (JURNAL KEPERAWATAN SISTHANA, 2021)
Diabetes mellitus type 2 is most often occurring and cause acute vascular diseases of vascular perifer and the loss of perifer blood circulation. One management of peripheral blood circulation in people with diabetes mellitus is to use diabetic feet spa therapy. The purpose of this case study is to describe the application of diabetic feet spa to peripheral blood circulation after and before therapy of diabetic feet spa. The type of the study belongs descriptive with a case study approach. The subjects of this study were two patients with type 2 diabetes mellitus, experienced mild peripheral blood circulation disorders who did not have ulcer wounds, and had the will and willing to follow a diabetic feet spa. Analysis of peripheral blood circulation was carried out descriptively and measured by the Ankle Brachial Index (ABI). The results of the case study showed that there was an increase in peripheral blood circulation subjects in both subjects, in subject I from 0.83 (mild) to 0.92 (normal) and in subject II from 0.88 (mild) to 0.95 (normal) after being done therapy for diabetic feet spa. It is suggested to Puskesmas officers need to treat spa diabetics as one of the peripheral blood circulation management in patients with type 2 diabetes mellitus.